The girl from the Grand Hotel : a novel - Aubray, Camille (Blackstone Publishing, 2024)
Set in summer 1939 at the Côte d'Azur's Grand Hotel and inspired by true events, Annabel Faucon is drawn into the events and intrigue surrounding a fledgling film festival, visiting movie stars, and efforts to disrupt a Nazi communications system.